2019
DOI: 10.1111/crj.13102
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of preoperative consolidation to maximum tumour diameter ratio and SUVmax in pathological stage I lung adenocarcinoma

Abstract: Objectives: Consolidation/tumour (C/T) ratio means the maximum diameter of the consolidation is divided by the maximum diameter of the tumour and it is predictive for pathologic subtypes and prognosis after resection of the tumour. The purpose of this study is to clarify impact of C/T ratio along with maximum standardized uptake value (SUV) in pathological stage I lung adenocarcinoma. Methods: Only patients with pathological stage I lung adenocarcinoma diagnosed by resection were included. Prognostic impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…All included studies were retrospective in our study. Most of the studies included were conducted in China and Japan; only two studies originated from Korea ( n = 2) [ 13 , 21 ] and one from Turkey ( n = 1) [ 30 ]. All included studies had an NOS score of at least 7 (with a mean value of 7.45), which meant they were all high-quality studies (Supplementary file Table S 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were retrospective in our study. Most of the studies included were conducted in China and Japan; only two studies originated from Korea ( n = 2) [ 13 , 21 ] and one from Turkey ( n = 1) [ 30 ]. All included studies had an NOS score of at least 7 (with a mean value of 7.45), which meant they were all high-quality studies (Supplementary file Table S 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed that the size of lung adenocarcinoma was relevant to SUVmax. [14][15][16] However, there is no clear conclusion about the relationship between T staging and SUVmax. Therefore, the study of the relationship between…”
Section: Introductionmentioning
confidence: 99%